2014
DOI: 10.1093/cercor/bhu156
|View full text |Cite
|
Sign up to set email alerts
|

Satb2 Regulates the Differentiation of Both Callosal and Subcerebral Projection Neurons in the Developing Cerebral Cortex

Abstract: The chromatin-remodeling protein Satb2 plays a role in the generation of distinct subtypes of neocortical pyramidal neurons. Previous studies have shown that Satb2 is required for normal development of callosal projection neurons (CPNs), which fail to extend axons callosally in the absence of Satb2 and instead project subcortically. Here we conditionally delete Satb2 from the developing neocortex and find that neurons in the upper layers adopt some electrophysiological properties characteristic of deep layer n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(162 citation statements)
references
References 62 publications
11
147
1
Order By: Relevance
“…We performed a novel analysis of the original spatio-temporal human brain transcriptome data set, using TSHZ3 as a seed, to identify the 49 genes whose expression profiles show the highest correlation with TSHZ3 in the developing neocortex. This TSHZ3 network contains 34 ASD candidate genes, out of which 6 encode transcription factors that are key regulators of CPN identity and connectivity: TBR1 16,17 , FEZF2 14,18 , FOXG1 13 , SATB2 19,21 , SOX5 31,32 and MEF2C 33,34 ( Supplementary Fig. 1a,b and Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We performed a novel analysis of the original spatio-temporal human brain transcriptome data set, using TSHZ3 as a seed, to identify the 49 genes whose expression profiles show the highest correlation with TSHZ3 in the developing neocortex. This TSHZ3 network contains 34 ASD candidate genes, out of which 6 encode transcription factors that are key regulators of CPN identity and connectivity: TBR1 16,17 , FEZF2 14,18 , FOXG1 13 , SATB2 19,21 , SOX5 31,32 and MEF2C 33,34 ( Supplementary Fig. 1a,b and Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that callosal and subcerebral axons failed to reach their targets in the Satb2 mutant mice (16)(17)(18)25). To investigate the molecular underpinning of these defects, we performed gene expression analysis of Satb2 lacZ/lacZ cortices by using RNA sequencing (RNA-seq).…”
Section: Misregulated Gene Expression In Satb2mentioning
confidence: 99%
“…Previous studies using mouse models revealed that SATB2 was essential for specifying callosal neuronal fate by repressing subcerebral identity in these cells (17)(18)(19)24). Intriguingly, a recent paper reported that SATB2 is also required for the development of subcerebral axons (25). However, it remains unknown how SATB2 performs two seemingly opposing functions.…”
mentioning
confidence: 99%
“…Satb2 is a DNA binding protein that interacts with nuclear matrix attachment regions and controls gene expression and chromatin remodeling. Functional studies of Satb2 have identified roles for this gene in musculoskeletal development, and shown this factor is necessary for establishing the proper identity and axon projections of callosal neurons (Alcamo et al, 2008; Britanova et al, 2008; Dobreva et al, 2006; Leone et al, 2014; Zhao et al, 2014). Interestingly, case studies of human mutations in the Satb2 gene have reported developmental delays in motor skill acquisition, coordination, and sensorimotor behavior (Balasubramanian et al, 2011; FitzPatrick et al, 2003; Van Buggenhout et al, 2005).…”
Section: Introductionmentioning
confidence: 99%